2022
DOI: 10.3389/fpsyg.2022.956281
|View full text |Cite
|
Sign up to set email alerts
|

Digital Students’ Satisfaction With and Intention to Use Online Teaching Modes, Role of Big Five Personality Traits

Abstract: During the COVID-19 pandemic, online teaching modes were found vital to continue students’ learning process, but sustainable implementation of online teaching models is an area of concern for policymakers. Psychiatrists are also eager to know students’ behavior toward learning and modes of teaching during COVID-19. We have drawn a model based on the big five personality traits to study students’ satisfaction with online teaching modes and their adoption intentions toward online teaching modes. We have collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…A recent study found that consumers of the male gender tend to place a higher priority on quality, in contrast to females, who are more likely to be affected by social factors while making purchases. Compared to their male counterparts, females have a greater awareness of prices (Mustafa et al, 2022a). According to the findings of this body of research, gender does have a role in customers' decision-making process.…”
Section: Gender Difference In Consumers' Psychementioning
confidence: 80%
See 4 more Smart Citations
“…A recent study found that consumers of the male gender tend to place a higher priority on quality, in contrast to females, who are more likely to be affected by social factors while making purchases. Compared to their male counterparts, females have a greater awareness of prices (Mustafa et al, 2022a). According to the findings of this body of research, gender does have a role in customers' decision-making process.…”
Section: Gender Difference In Consumers' Psychementioning
confidence: 80%
“…In order to have a better understanding of how consumers purchase eco-friendly products in developing countries, we have selected these characteristics from UTAUT. In the past, researchers have used this theory in various contexts, such as buying smartwatches (Mustafa et al, 2022a) 5G technology (Mustafa et al, 2022b) etc. Based on UTAUT, we have developed a model and integrated environmental knowledge to study the developing countries' users' behavioural intentions towards eco-friendly products.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 99%
See 3 more Smart Citations